LITERASI INTERNET PETANI WILAYAH PERSEN TEGALDLIMO DALAM RANGKA IMPLEMENTASI SAWAH DIGITAL DI KABUPATEN BANYUWANGI JAWA TIMUR - Fiqru Mafar (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
The Digital Rice Field Implementation plan in Banyuwangi Regency East Java is one of current breakthroughs to pursue food security in the area. This study is aimed at finding out the readiness of farmers in Persen Tegaldino area of Banyuwangi Regencyas the users of Digital Rice Field information. Data is collected by conducting a survey to 100 farmer respondents in Persen Tegaldino. The result of this study shows that Internet literacy among farmers in the area is extremely low, indicated by the finding that 82% of the farmers cannot use the Internet. Looking at this condition, it is suggested that the government run courses and trainings for farmers in the area to use the Internet.